123 Systematic review and meta-analysis comparing bilateral versus single internal thoracic artery grafts in patients with diabetes and obesity undergoing coronary artery bypass graft surgery. (17th July 2020) - Flather, Marcus; Stefil, Maria; Gaudino, Mario; Benedetto, Umberto; Gray, Alastair; Gerry, Stephen; Lees, Belinda; Krzych, Lukasz; Seevanayagam, Siven; Taggart, David
Abstract : Background: Obesity and diabetes put patients are at higher risk of mortality and other adverse outcomes following coronary artery bypass grafting (CABG) and are becoming more common. The use of bilateral internal thoracic arteries (BITA) can potentially offer survival benefit in higher risk patients compared to single internal thoracic artery (SITA) in patients undergoing CABG. Current evidence does not support the routine use of BITA and this approach is associated with a higher risk of sternal wound complications. Methods: We conducted a systematic review of the literature to identify observational studies and randomised controlled trials (RCT) comparing efficacy (mortality) and safety (sternal wound infection) of BITA and SITA in diabetic and obese patients. Results: Eighteen observational studies and one RCT (subgroup analysis) were identified comparing BITA and SITA in 19, 589 patients with diabetes. In contrast there were just two observational studies and one RCT (subgroup analysis) comparing BITA and SITA in 6972 obese patients. Pooled analysis demonstrated significant mortality benefit of BITA compared to SITA in diabetic patients (risk ratio [RR] 0.79; 95% confidence interval [CI] 0.70, 0.90; Z=3.62, p=0.0003; I2=88%) (Figure 1b ). Pooled analysis in obese patients found no significant difference in mortality rates between BITA and SITA (RR 0.73, 95% CI 0.47, 1.12; Z=1.43, p=0.15; I2=78%), although the overall effect was for a beneficial trend for BITA (Figure 1a ). A significantly higher rate of sternal wound complications following BITA was observed in diabetic (RR 1.53, 95% CI 1.23, 1.90; Z=3.86, p=0.0001; I2=4%) and obese patients (RR 2.24, 95% CI 1.63, 3.07; Z=5.00, p<0.00001; I2=0%). Conclusions: In a pooled analysis, BITA is associated with better long-term survival in diabetic patients, but most of the supportive data comes from observational studies. The effects of BITA grafting in patients who are obese is uncertain due to low numbers of patients available for analysis. BITA is associated with higher rates of sternal wound complications than SITA in both diabetic and obese patients. Further studies are needed to understand the benefits and risks of multiple arterial grafting in patients with diabetes and/or obesity. Conflict of Interest: None